Characterization of the effects of cross-linking of macrophage CD44 associated with increased phagocytosis of apoptotic PMN. - Simon P Hart; Adriano G Rossi; Christopher Haslett; Ian Dransfield (PLoS ONE, 2012)
Control of macrophage capacity for apoptotic cell clearance by soluble mediators such as cytokines, prostaglandins and lipoxins, serum proteins, and glucocorticoids may critically determine the rate at which inflammation resolves. Previous studies suggested that macrophage capacity for clearance of apoptotic neutrophils was profoundly altered following binding of CD44 antibodies. We have used a number of different approaches to further define the mechanism by which CD44 rapidly and specifically augment phagocytosis of apoptotic neutrophils. Use of Fab' fragments unequivocally demonstrated a requirement for cross-linking of macrophage surface CD44. The molecular mechanism of CD44-augmented phagocytosis was shown to be opsonin-independent and to be distinct from the Mer/protein S pathway induced by glucocorticoids and was not functional for clearance of apoptotic eosinophils. CD44-cross-linking also altered macrophage migration and induced cytoskeletal re-organisation together with phosphorylation of paxillin and activation of Rac2. Investigation of signal transduction pathways that might be critical for CD44 augmentation of phagocytosis revealed that Ca(2+) signalling, PI-3 kinase pathways and altered cAMP signalling were not involved, but did implicate a key role for tyrosine phosphorylation events. Finally, although CD44 antibodies were able to augment phagocytosis of apoptotic neutrophils by murine peritoneal and bone marrow-derived macrophages, we did not observe a difference in the clearance of neutrophils following induction of peritonitis with thioglycollate in CD44-deficient animals. Together, these data demonstrate that CD44 cross-linking induces a serum opsonin-independent mechanism of macrophage phagocytosis of apoptotic neutrophils that is associated with reduced macrophage migration and cytoskeletal reorganisation.